Photogrammetry and 3D laser scanning as spatial data capture techniques for a national craniofacial database - Majid, Zulkepli; Chong, Albert K; Ahmad, Anuar; Setan, Halim; Samsudin, Abdul Rani (2005)
Photogrammetry is a non-contact,high-accuracy,practical and cost-effective technique for a large number of medical applications.Lately,three-dimensional (3D) laser scanning and digital imaging technology have raised the importance of digital photogrammetry technology to a new height in craniofacial mapping.Under the support of the Eighth Malaysian Development Plan,the Ministry of Science, Technology and the Environment (MOSTE)Malaysia allocated a grant to establish procedures for the development of a national craniofacial spatial database to assist the medical profession to provide better health services to the public.To populate the database with normal and abnormal (malformation,diseased and trauma and burn victims)craniofacial information,it is necessary to evaluate the technology needed to capture the essential data of craniofacial features. The paper provides a discussion on the basic features of the spatial data and the data capture techniques.Both are needed for the establishment of a national spatial craniofacial database.The discussion includes a brief review of the current status of two selected high-accuracy craniofacial spatial data capture techniques,namely, digital photogrammetry and 3D laser scanning.The paper highlights a system which has been developed for a Malaysian craniofacial mapping project. Laboratory tests with mannequins showed that the photogrammetric and 3D laser scanning system could achieve an accuracy exceeding the design speci ï¬?cation of Â±0 Ã† 7 mm (one standard deviation)for all the measured craniofacial distances. However,tests with two living subjects showed that the accuracy was in the order of Â±1 Ã† 2 mm because of facial movement during data capture.